Applications and prospects of phosphoproteomics in renal disease research - XueJia Zheng; LingLing Zhou; TianTian Xu; GuoYing Wang; YaLi Peng; ChunMei Wen; MengYao Wu; HuiHui Tao; Yong Dai (PeerJ)
Introduction Phosphoproteomics, an advanced branch of molecular biology, utilizes specific techniques such as mass spectrometry, affinity chromatography, and bioinformatics analysis to explore protein phosphorylation, shedding light on the cellular mechanisms that drive various biological processes. This field has become instrumental in advancing our understanding of renal diseases, from identifying underlying mechanisms to pinpointing new therapeutic targets. Areas covered This review will discuss the evolution of phosphoproteomics from its early experimental observations to its current application in renal disease research using liquid chromatography-tandem mass spectrometry (LC-MS/MS). We will explore its role in the identification of disease biomarkers, the elucidation of pathogenic mechanisms, and the development of novel therapeutic strategies. Additionally, the potential of phosphoproteomics in enhancing drug discovery and improving treatment outcomes for renal diseases will be highlighted. Expert opinion Phosphoproteomics is rapidly transforming renal disease research by offering unprecedented insights into cellular processes. Utilizing techniques such as LC-MS/MS, it enables the identification of novel biomarkers and therapeutic targets, enhancing our understanding of drug mechanisms. This field promises significant advancements in the diagnosis and treatment of renal diseases, shifting towards more personalized and effective therapeutic strategies. As the technology evolves, its integration into clinical practice is pivotal for revolutionizing renal healthcare.